ANALYSIS OF ZOOXANTHELLA DENSITY ON CORAL Acropora sp IN SIRONJONG GADANG ISLAND PESISIR SELATAN DISTRICT WEST SUMATRA - Jefri Affandi; Thamrin '; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis research was conducted in September 2014 in the island of Sironjong Gadang, Koto XI Tarusan, Pesisir Selatan Disctrict of West Sumatra Province. The purpose of this study is to know the effect of depth towards the density of zooxanthella on the type of coral Acropora sp in Seronjong Gadang Island. While the benefits of the research are expected to obtain data and information about the density of zooxanthella on Acropora sp at the different depths. The methodology used in this research was a survey method and for coral sampling used purposive sampling technique, where samples are taken around the Seronjong Gadang Island with 3 different depth according to distribution of Acropora sp Coral reef that surround these waters. Parameter measurements of waters performed at each station. Samples were taken in the field, then followed by analyzing samples in the Laboratory.Depth is one of factor that affect the amount of light intensity that enters into the waters. The light that comes into the waters was symbion zooxanthella needed to perform fotosentesis in his life as the main supplier for coral as host. The deeper the waters, the less light that come into the waters. According to the research, there is the difference between the depth of 1 m, 5 ms and 10ms. The average of Zooxanthella cell in the depth of 1 m are 5.150.125 cell/cm2, then in the depth of 5 m are 3.552.525 cell/cm2, and in the depth of 10 m the average of zooxanthella are 3.242.241 cell/cm2. It means that the amount of Zooxnthella on Acropora sp decreased over by the increase of the depth.Keywords: Coral, Acropora sp, zooxanthella, Sironjong Gadang.